Languages and compilers for parallel computing : 27th International Workshop, LCPC 2014, Hillsboro, OR, USA, September 15-17, 2014, Revised selected papers /: 27th International Workshop, LCPC 2014, Hillsboro, OR, USA, September 15-17, 2014, Revised selected papers. (2015) - Unknown
No abstract available